Emerging breakthroughs in membrane filtration techniques and their application in agricultural wastewater treatment: Reusability aspects - R. Kamalesh; S. Karishma; A. Saravanan; P.R. Yaashikaa (Sustainable Chemistry for the Environment)
Freshwater resources are becoming limited and are rapidly getting polluted due to industrialization and urbanization. Water pollution is a pervasive global challenge both in terms of scarcity and quality. Among other sources, wastewater discharged through agricultural practices are major contributor to environmental pollution. The leading cause of contaminants is the runoff of fertilizers, herbicides, insecticides and animal waste into waterbodies. Conventional treatment methods efficiently remove large particles, organic matter, and nutrients but require extensive infrastructure and produce significant sludge. In contrast, membrane filtration offers superior purification and reuse potential by using semi-permeable membranes to selectively remove contaminants, including suspended solids and dissolved ions. This study examines membrane filtration principles and technologies, emphasizing their role in delivering high-quality effluent for discharge or reuse. The study identifies fertilizers, herbicides, and insecticides as major agricultural contaminants and highlights conventional techniques' ineffectiveness in achieving high purification levels. Membrane filtration effectively remediates a wide range of pollutants, but fouling remains a challenge, addressed by antifouling agents and advanced membrane materials in hybrid processes. The study concludes by highlighting the reusability aspect of membrane filtration in agricultural systems and the potential applications of reclaimed water. This study emphasizes the need for advanced membrane materials and integrated systems for effective utilisation of membrane filtration.